Editorial - Chau, Meng Huat (Journal of Modern Languages, 2021)
Welcome to the December 2021 issue, which concludes Volume 31. We have a full issue for you again, comprising six articles spanning applied and theoretical explorations of language. This issue contains contributions from a variety of teaching and research contexts ranging from the classroom to the Instagram ecology. The topics explored range from the need to expand students’ choices and salient aspects of bilingual dictionaries of Islamic finance and economy to strategies employed by politicians to respond to interviewers’ face-threatening questions, and the phonological distribution of nasalized consonants and nasalized vowels in the Mbaise dialect of Igbo. The articles focus on the practical and theoretical relevance of the topics that the authors examined. Together they reflect current issues confronting language teachers and researchers in applied and theoretical linguistics, and the ways these issues can be explored and described. This concluding issue of 2021 has special significance for me as it marks the final issue in my role as Editor-in-Chief. I have decided to step down to focus on other commitments. I must note that I have been privileged to be able to witness the growth of the Journal over the past few years, and am particularly pleased to see that we now receive over twice as many submissions per year as we had when I first took up the role in 2019. As readers of this Journal have noticed, starting from 2020, we have also started to publish two issues per year. This is not just a matter of growth in terms of quantity of production; the quality of the articles published can also be seen from the range of topics addressed and the geographical distribution of our authors. Almost half of the articles of each issue published came from authors outside Malaysia, and they were received from such countries as India, Indonesia, Iran, Iraq, Japan, Nigeria, Singapore, Spain, the Philippines and the UK. All this was made possible with the strong support and positive energy of the entire editorial team and our International Advisory Board. I would like to take this opportunity to record my heartfelt thanks to all the members of the Editorial Board and Advisory Board for their contributions during this period of three meaningful years with me: Associate Editor Chew Shin Yi (Universiti Malaya, Malaysia) Editorial Board Mohd Ridwan Abdul Wahid (Universiti Malaya, Malaysia) Ang Pei Soo (Universiti Malaya, Malaysia) Thanalachime Perumal (Universiti Malaya, Malaysia) Stefanie Pillai (Universiti Malaya, Malaysia) Hang Su (Sichuan International Studies University, China) Benet Vincent (Coventry University, United Kingdom) Toshiko Yamaguchi (Universiti Malaya, Malaysia) Lee Kok Yueh (Universiti Teknologi Brunei, Brunei Darussalam) Azlin Zaiti Zainal (Universiti Malaya, Malaysia) International Advisory Board Shirley Dita (De La Salle University, Philippines) Richard Fitzgerald (University of Macau, China) Stephen Hall (Sunway University, Malaysia) Jan Hardman (University of York, United Kingdom) Michelle M. Lazar (National University of Singapore, Singapore) Jason Miin-Hwa Lim (Universiti Malaysia Sabah, Malaysia) Jonathan Newton (Victoria University of Wellington, New Zealand) Mario Pinharanda Nunes (University of Macau, China) Dennis Tay (The Hong Kong Polytechnic University) My special thanks also go to all the dedicated reviewers, contributors and readers of this Journal. I look forward to watching the Journal continue to grow in the capable hands of Dr Chew Shin Yi, the Editor-in-Chief for the Journal starting 2022. Shin Yi has worked very closely with me for the past three years, and I am most grateful to have her strongest support in managing this Journal together, particularly during this challenging period of COVID-19. All of us involved in the publication of this Journal wish you, our readers and families, good health and unlimited blessings. Chau Meng Huat For the editorial team